Estudio anatomo-histológico delsistemadigestivo de stenomacramarginella (herrich-schaeffer, 1850) (hemiptera: heteroptera: largidae) - Nava-Gervasio, Sheirla M.; Ortíz-Ordoñez, Esperanza; Uría-Galicia, Esther A. (Instituto de Ecología, A.C., 2007)
The anatomical and histological study of the digestive system of Stenomacra marginella (Herrich-Schaeffer 1850), was made, to know its adaptations and understand the digestive and adsorptive processes. The results show, that the digestive tube of this specie has the same general structural pattern that is characteristic of the insects, present the following differences with other sap sucker Hemiptera: absence of gastric caeca and peritrofhic membrane, presence of granular unicellular glandular cells and glandular tissue surrounding the midgut. This, together with the direct observations of feeding from diverse sources (organic waste and sap), suggest that this specie is omnivore and not phytophagous or poliphagous.